2008
DOI: 10.1152/ajpregu.00489.2007
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 40 and ATP-dependent intercellular calcium wave in renal glomerular endothelial cells

Abstract: Endothelial intracellular calcium ([Ca(2+)](i)) plays an important role in the function of the juxtaglomerular vasculature. The present studies aimed to identify the existence and molecular elements of an endothelial calcium wave in cultured glomerular endothelial cells (GENC). GENCs on glass coverslips were loaded with Fluo-4/Fura red, and ratiometric [Ca(2+)](i) imaging was performed using fluorescence confocal microscopy. Mechanical stimulation of a single GENC caused a nine-fold increase in [Ca(2+)](i), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 44 publications
4
70
0
Order By: Relevance
“…18 Because mesangial cells express several P2 receptors, 31 they may be activated by ATP released from the macula densa. Whether Cx40 primarily serves to connect mesangial cells, smooth muscle cells, or both 9,17,33 or acts as hemichannel to release further ATP from mesangial cells, as observed in cell culture, 34 warrants further investigation. In contrast, the myogenic component of the autoregulatory response is not different in Cx40-deficient and wt kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…18 Because mesangial cells express several P2 receptors, 31 they may be activated by ATP released from the macula densa. Whether Cx40 primarily serves to connect mesangial cells, smooth muscle cells, or both 9,17,33 or acts as hemichannel to release further ATP from mesangial cells, as observed in cell culture, 34 warrants further investigation. In contrast, the myogenic component of the autoregulatory response is not different in Cx40-deficient and wt kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…β-Blockers induce relaxation of the glomerular microvasculature by releasing ATP, which acts via P2Y receptors on endothelial cells to produce NO, resulting in vasodilation [180]. Connexin (Cx) 40 hemichannels and extracellular ATP are the key molecular elements of the glomerular endothelial calcium wave [371]. A review that discusses the roles of ATP and adenosine in tubuloglomerular feedback (TGF) regulation of glomerular filtration is available [46].…”
Section: Glomerulus and The Renal Vasculaturementioning
confidence: 99%
“…It has been shown that propagation of calcium waves in confluent monolayers of bovine corneal endothelial cells occurs in response to mechanical stimulation in which a glass micropipette is used to mechanically perturb the plasma membrane of a cell [125]. In these studies, ATP to the system [124]. Altogether, these different studies suggest that these endothelial cells express undocked connexin hemichannels at the plasma membrane, which are capable of releasing ATP in response to mechanical stimulation.…”
Section: Connexin Hemichannelsmentioning
confidence: 99%
“…To date, about 20 mammalian connexin isoforms have be identified, and the role of these proteins in gap junctional communication has been extensively characterized. However, there have been reports of undocked connexons or hemichannels at the surface of a number of cell types including astrocytes and glia in the central nervous system [119][120][121], circulating polymorphonuclear granulocytes [79] and monocytes [122], vascular endothelial cells [22,[123][124][125] and vascular smooth muscle cells [126]. It has been proposed that these hemichannels may function as conduits for the transport of molecules, including ATP, between the cytosol of a cell and the extracellular space [127,128].…”
Section: Connexin Hemichannelsmentioning
confidence: 99%
See 1 more Smart Citation